Modal Sosial Kelompok Tani “Lamo Jaya” di Desa Pinaling Kecamatan Amurang Timur Kabupaten Minahasa Selatan - Sabanari, Aneke; Porajouw, Oktavianus; Timban, Jean Fanny Junita (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This study aims to determine the development of social capital of Lamo Jaya farmer group in Pinaling Village, East Amurang Sub-district, South Minahasa Regency. The research was conducted in a period of 3 months from May to July 2022. The data used in this study were obtained through interviews with 20 farmer group members as research respondents. The data collected were analyzed descriptively using Likert Scale measurements. The results showed that the social capital of the Lamo Jaya farmer group was in the high category, with an index number of 68.8%. Social capital is high, because the level of member trust, social networks and social norms are in the high category